Musiqiy ash'ar Ibn Rashiq fi kitab "Ibn Rashiq al Qayruniy" li Muhammad Salamah Yusuf Rahmat [ Dirasah tahliliyyah 'urudiyyah - Muhammad Ferry Ulla (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2014)
khus, 1/ws.c.1